Uncovering a suppressor effect in the relationship between psychological capital and employment expectations: a chain mediation model among vocational undergraduates - Huang, Zerui; Ismail, Ismi Arif; Ghazali, Akmar Hayati Ahmad; D'Silva, Jeffrey Lawrence; Abdullah, Haslinda; Zhang, Zeqing (Frontiers in Psychology, 2025)
PurposeThis study investigates the relationship between psychological capital and employment expectations among vocational undergraduate students, with a particular focus on the mediating roles of educational flow experience and active coping style.MethodsData were collected through a questionnaire survey administered to 693 vocational undergraduate students at a university in Guangdong Province, China. The instruments used included the Positive Psychological Capital Scale (PPS), Career Expectation Scale (CES), Educational Flow Scale (EduFlow-2), and Coping Style Scale (CSS).Results(1) Psychological capital was found to exert a significant positive influence on employment expectations, educational flow experience, and active coping style. (2) Both educational flow experience and active coping style played significant mediating roles in a chain mediation model. Furthermore, a suppressor effect was identified in the mediation process.ConclusionThis study confirms the significant influence of psychological capital on employment expectations and elucidates its underlying mechanisms. It highlights the critical roles of educational flow and active coping in shaping students' employment outlook, offering practical insights for enhancing employment outcomes among vocational undergraduates.